Impact of remnant cholesterol to high-density lipoprotein cholesterol ratio on risk of incident ASCVD: the Kailuan prospective cohort study - Yizhen Tan; Shuohua Chen; Zhe Huang; Xiangfeng Lu; Jianxin Li; Youxin Wang; Shouling Wu; Ying Wu; Yuntao Wu; Yun Li (Nutrition & Metabolism)
Abstract Background The study utilized the remnant cholesterol (RC) to high-density lipoprotein cholesterol (HDL-C) ratio as a lipidemia indicator. Assessing its long-term impact on cardiovascular disease (ASCVD) is crucial for primary prevention. Methods 84,380 participants were enrolled in the prospective cohort. Participants were classified into low, medium, and high levels based on baseline RC/HDL-C levels at the 50th percentile and 90th percentile. Participants were followed until December 31, 2023. Calculate the incidence density of ASCVD for each group. The time-dependent Cox proportional hazards model was utilized to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) for ASCVD risk among different groups. Results The study included 42,181, 33,739, and 8460 participants in the low, medium, and high levels respectively. A median follow-up of 16.92 years, 8397 ASCVD cases were identified. The 1000 person-years incidence density and 95% CIs for ASCVD were 5.86 (5.67, 6.05) in the low level, 6.92 (6.70, 7.15) in the medium level, and 8.85 (8.35, 9.39) in the high level. Compared to the low level, the Cox model showed that the HRs and 95% CIs for ASCVD were 1.09 (1.04, 1.14) and 1.23 (1.15, 1.32), respectively in medium and high levels. Conclusion Higher RC/HDL-C level was significantly associated with an increased risk of ASCVD. Including the RC/HDL-C in lipid evaluation can reduce the onset of ASCVD. Clinical trial registration number ChiCTR2000029767.